100 anos de Florestan Fernandes legado de ciência e militância - Totti, Marcelo Augusto (Editora Oficina Universitária, 2022)
Florestan Fernandes would be 100 years old in 2020. Son of Maria Fernandes, a Portuguese immigrant who came to work on Brazilian farms, he has known the hardships of life since childhood, according to his own words he would never have become the sociologist he was, without his "plebeian" origin and their pre- and extra-school socialization. This sociological learning began at the age of 6 when he needed to earn a living as an adult, working as a shoeshine boy. But I would say that it is earlier, his mother, disillusioned with working in the fields of the interior of São Paulo, decides to move to the capital and starts to work as a domestic in the Bresser family home. Pregnant with Florestan, Hermínia Bresser de Lima, who would be Florestan's godmother, of wealthy origins and with refined habits, refused to call him by the name Florestan, the name of origin German, the result of a character in a Beethoven opera, was not a name for a laundress's son, so the godmother "renames him" calling him Vicente. Florestan had lived another sociological experience, which is the prejudice of the Brazilian elites towards the Brazilian people coming from the subordinate classes. Florestan studied this prejudice in more depth in his research on racial relations and the insertion of black people in class society, identifying the historical and structural origins of racism in Brazil that go back to our heritage of a slave-owning past. He faced difficulties like a large part of the Brazilian population, he worked as a waiter at Bidu's bar, read behind the counter at times of less movement, which aroused the interest of teachers who frequent the place. The encouragement of the teachers who attended there bore fruit, he studied at the old maturity course and through one of those regulars at that bar, he got a job at a chemical company, enabling better socioeconomic conditions. The difficulties for young people of "plebeian" origin would not be limited there, the challenge of entering higher education was something very distant. The newly created University of São Paulo, public and free, was an alternative. Created by the elites and for the elites, the entry of a working student with training in a maturity course contrasted with the aristocratic and erudite tone of the professors and students of the São Paulo elite. To remedy what he called a cultural deficit, he undertakes a monastic study routine that included reading on streetcars, park benches and staying in the municipal library until the lights went out. Passing the entrance exam was not the easiest, with a panel composed of two French professors, with an oral test in French of a book by a French sociologist, it seemed an almost insurmountable barrier for the graduate of the maturity course. Florestan read in French and knew Durkheim's book On the Division of Social Work well and asked to take the test in Portuguese, the defendants found the situation unusual, but they accepted the candidate's request, which was approved (of the 29 competitors, only 6 were approved) . Florestan Fernandes was not just a survivor, he was a winner! He rowed against the tide in turbulent seas, faced themes and research that were not used in sociology at the time, printed a model of sociological science, placing sociology alongside the problems claimed by society. He fought for the public school, for the public university, he was on the side of the disinherited of the land, a socialist militant, his mandate as deputy functioned as a form of tribune of the plebs: a voice for those who have no voice. In a society like Brazil marked by serious structural problems, ethnic, racial and social inequalities, the ideas and writings of Florestan Fernandes are more than necessary and remain alive in the struggle of the workers, at the National School of the Landless Workers Movement that bears his name, in public schools, public universities, in debates and this book intends to be one more contribution to keep the flame of his ideas burning, which light the way of an obscure past and guide to an alternative future of utopia and hope for Brazilian society. FLORESTAN FERNANDES, Always Present!